A Study On Health Status Of Children Under Five Years Of Age In A Rural Village Of Eastern Part Of Nepal - Adhikari, Dewa (Journal of Nobel Medical College, 2013)
Introduction: Every needy child should receive the best medical and surgical attention. In 1940, the White house Conference proposed adequate health services including medical and dental examination, immunization and early detection and treatment of diseases, vision and hearing tests, prevention and control of disease, health records and health services facilities. Objectives: To assess the health status of under five children. To know the treatment preference of the parents towards their sick children. To initiate control measures early, by allocating the health resources more efficiently and providing health awareness activities. Materials and Methods: Descriptive cross-sectional study was conducted. The entire 1-5 years age child (40children) residing in Dharan Municipality ward. No-17 at Phoklen Tapu was included. Simple random sampling technique (lottery method) was used to select the village and Census survey technique was followed to find out the 1-5 years children. The survey was conducted by investigator herself and self develop tools were used to health status of the child. Results: Most of the morbid conditions founded in the study were related to skin diseases (ring worm, boils/wound, cuts, eczema/ redness), ear infection, enlarged lymph node, Pneumonia, Diarrhoea/ vomiting, abdominal enlargement and malnutrition with different Grade. Conclusion: Majority of the parent were not having health education regarding child care. The treat their child with home remedies, by faith healer then after third time they seek sick child with health personnel. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 49-54 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7676